Population status and impact of climate change on the distribution of vulnerable multipurpose plant Hippophae rhamnoides ssp. turkestanica for conservation in Trans-Himalaya, India - Paul, Shiv; Kanwal, Khilendra Singh; Kumar, Anil; Samant, Sher Singh; Bhatt, Indra Dutt; Sundriyal, Rakesh Chandra; Lata, Swaran (Frontiers in Forests and Global Change, 2025)
The populations of globally significant species in the Himalaya are invariably shrinking due to multiple forms of human manipulation. Over the decades, various species’ natural habitats have been influenced by changing climate patterns, and the trends are consistently increasing, which is an issue of concern. The Hippophae rhamnoides ssp. turkestanica Rousi is a critical species native to the Himalaya, belonging to the Elaeagnaceae family. It is widely known for its significant ecological, economic, and social benefits. There is a great need to conserve this species in the cold desert region to improve the livelihood and socioeconomic status of tribal communities. Therefore, the current study aims to assess the population status and predict highly suitable areas for Trans-Himalaya species under changing climatic conditions. The machine learning algorithm showed that Bio_6 (minimum temperature of the coldest month), elevation, and slope were the best suitable variables for the habitat prediction along with the CMIP6 project’s MIROC6 and CMCC-ESM2 climate change models to identify the potential distribution area of the species for the future under the SSP245 (middle of the way) and SSP585 (fossil-fueled development) scenarios, respectively. The result found that a 2.20% (4,028 km2) area is highly suitable for the species’ occurrence. The potential suitability areas of the species are predicted to expand along the boundary of the present distribution areas at the pace of climatic change. The current study findings will help to determine the species resource reserve in the Trans-Himalaya. The predicted distribution maps of the species would help policymakers and decision-makers design appropriate management and sustainable utilization approaches in the near future.